Exercise and quality of life during and after treatment for breast cancer: results of two randomized controlled trials. - Cadmus, Lisa A; Salovey, Peter; Yu, Herbert; Chung, Gina; Kasl, Stanislav; Irwin, Melinda L (Psycho-oncology, 2009)
To determine the effect of exercise on quality of life in (a) a randomized controlled trial of exercise among recently diagnosed breast cancer survivors undergoing adjuvant therapy and (b) a similar trial among post-treatment survivors.
Keywords: Adult; Aged; Anxiety; Breast Neoplasms; Depression; Exercise; Female; Happiness; Humans; Middle Aged; Psychology; Quality of Life; Questionnaires; Self Concept; Stress, Psychological